Health Empowerment, and Economics of Women with HIV/AIDS Through Life Skills Education - Awatiful Azza; Trias Setyowati; Fauziah Fauziah (Universitas Airlangga, 2015)
Introduction: Women with HIV/AIDS have a heavy burden. Discrimination and the low economic status causes them worse off in the uncertainty of life. The purpose of the study to develop a health empowerment and economic and increase community involvement in the business activities of women with HIV/AIDS.Methods: The method descriptive approach,focus group discussion. The preparation of the design strategies, health empowerment and economic through life skills education for women with HIV/AIDS strengthened through Participatory Action Research (PAR).Results:The results of this study showed that the health status of women with HIV who are involved in phase I. The average age of patients were at a fairly productive life span between 20–40 years. 90% they do not have income. The results of focus group discussions (FGD) indicates that the client requires additional activities that can generate income, but do not overload the physical. Some of the selected activities include embroider and sew, salons and cooking. the result of research on public response associated with HIV/AIDS they mention that women with HIV should be protected by the government and the public, although on average they still can not accept people in their environment.